1972
DOI: 10.1111/j.1365-3083.1972.tb01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement‐Fixing Intracellular Complexes of IgG Rheumatoid Factor in Rheumatoid Plasma Cells.

Abstract: Intracellular rheumatoid factor activity is found mostly in IgM plasma cells of rheumatoid synovial membranes from seropositive patients, while tissues from seronegative patients nearly always lack free rheumatoid factor. However, rheumatoid factor activity can be revealed in a considerable number of IgG plasma cells by pepsin digestion of tissues both from seropositive and seronegative patients. This activity has been further characterized by sequential double immunofluorescence staining. It was demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
129
3

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 14 publications
9
129
3
Order By: Relevance
“…In the 8 cultures in which IgG-RF was detectable, it represented a mean of 2.6% of the total synthesized IgG. Thus, our data are not in agreement with the results of immunofluorescence studies of synovium (1,6,24), in which IgG-RF was detected by staining in 20-60% of IgG-producing plasma cells. It is unlikely that our assay underestimated the amount of IgG-RF, since the method was standardized against a preparation of polyclonal IgG-RF that had been rigorously purified from the serum of a patient with RA (12).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In the 8 cultures in which IgG-RF was detectable, it represented a mean of 2.6% of the total synthesized IgG. Thus, our data are not in agreement with the results of immunofluorescence studies of synovium (1,6,24), in which IgG-RF was detected by staining in 20-60% of IgG-producing plasma cells. It is unlikely that our assay underestimated the amount of IgG-RF, since the method was standardized against a preparation of polyclonal IgG-RF that had been rigorously purified from the serum of a patient with RA (12).…”
Section: Discussioncontrasting
confidence: 98%
“…IgG-RF-producing cells were demonstrated in all of 3 seronegative RA samples in 1 study (1 l), but in neither of 2 seronegative samples in the other (10). Munthe and Natvig (1,6) found that there was binding of fluoresceinated aggregated IgG to 50-75% of plasma cells of seronegative and to 25-50% of plasma cells of seropositive RA synovium after pepsin digestion. They concluded that there is extensive synthesis of self-associating IgG-RF in seropositive and seronegative rheumatoid synovial tissue.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, B cells in all stages of differentiation, from mature B cells to plasma cells, have been observed (16)(17)(18)(19)(20). There is some molecular evidence that B cells are specifically activated and clonally expanded in the synovium (21)(22)(23).…”
mentioning
confidence: 99%
“…Idiotype-positive peripheral blood B cells may be precursors of the plasma cells that are localized in joint tissue and are producing RF (22,23). Furthermore, the positive migration inhibition with aggregated IgG in rheumatoid arthritis (24) may indicate R F idiotype-positive T cells.…”
Section: Discussionmentioning
confidence: 99%